Evaluation of different fungicides (chemical, botanical and bio-agent) in controlling wheat blast in a blast prone area in Bangladesh. (4th August 2021) - Roy, Krishna Kanta; Anwar, Md Babul; Mustarin, Kishowar-E-; Reza, Md Mostofa Ali; Muzahid-E-Rahman, Md; Malaker, Paritosh Kumar; Barma, Naresh Chandra Deb; Singh, Pawan Kumar
Abstract: This study aimed to evaluate the performance of different fungicides (chemical, botanical and bio-agent) against wheat blast under field conditions and to identify the best one for preventive spray. Among the fungicides evaluated, Nativo 75 WG (Tebuconazole 50% + Trifloxystrobin 25%), Amistar Top 325 SC (Azoxystrobin 20% + Difenoconazole 12.5%) and Cabrio Top 60 WG (Pyraclostrobin 5% + Metiram 55%) demonstrated the best results with least blast severity (4–8%) and the highest yield (78–88%). It was concluded that the mentioned fungicides can be used to control wheat head blast by spraying twice at 13–15 days interval starting with the heading stage.